2019
DOI: 10.1177/1535370219878651
|View full text |Cite
|
Sign up to set email alerts
|

Berberine protects steatotic donor undergoing liver transplantation via inhibiting endoplasmic reticulum stress-mediated reticulophagy

Abstract: Steatotic livers are more susceptible to ischemia/reperfusion injury, and increase the risk of primary graft non-function after liver transplantation. The protective effects of berberine have been described in various liver pathological models. However, it is unknown if berberine exerts its beneficial action in steatotic donors undergoing liver transplantation. In the present study, male Wistar rats were fed with high-fat diet (HFD) for 12 weeks to induce moderate steatotic liver. Then orthotropic liver transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Furthermore, under these conditions, the pharmacological inhibition of autophagy protected steatotic liver grafts. This study also generated another important result in the setting of transplantation: in steatotic grafts, berberine inhibited autophagy and protected the graft, but the same drug activated autophagy in optimal grafts and decreased liver injury (Lin et al, 2017;Zhang et al, 2019). This observation underscores the very different signaling mechanisms that act in optimal vs. steatotic grafts, despite being subjected to the same surgical maneuvers.…”
Section: Autophagy In Livers Affected By Metabolic Diseases and Undergoing Surgerymentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, under these conditions, the pharmacological inhibition of autophagy protected steatotic liver grafts. This study also generated another important result in the setting of transplantation: in steatotic grafts, berberine inhibited autophagy and protected the graft, but the same drug activated autophagy in optimal grafts and decreased liver injury (Lin et al, 2017;Zhang et al, 2019). This observation underscores the very different signaling mechanisms that act in optimal vs. steatotic grafts, despite being subjected to the same surgical maneuvers.…”
Section: Autophagy In Livers Affected By Metabolic Diseases and Undergoing Surgerymentioning
confidence: 66%
“…Very few experimental studies have evaluated the role of autophagy in transplantation of NAFLD grafts (Gracia-Sancho et al, 2013;Zaouali et al, 2013aZaouali et al, ,b, 2017Panisello-Roselló et al, 2017Zhang et al, 2019). To date, reported results differ depending on the experimental model used.…”
Section: Autophagy In Livers Affected By Metabolic Diseases and Undergoing Surgerymentioning
confidence: 99%
“…For instance, resveratrol can affect the ER to exert its therapeutic impacts [116]. This story is also similar for curcumin [62], berberine [80], emodin [122] and other natural products. So, it is conspicuous that organelles can be considered as potential targets of these natural products.…”
Section: Regulation Of Mitochondria By Plant-derived Chemicalsmentioning
confidence: 86%
“…The structure of mitochondria is of importance in induction or inhibition of apoptotic cell death [77,78]. Accumulating data demonstrates that mitochondria are the central gateway of the intrinsic pathway of apoptosis [79,80]. This reveals the potential role of mitochondria in the regulation of life and death [81,82].…”
Section: Mitochondria and Apoptosismentioning
confidence: 99%
“…Zhang et al found that berberine (BBR), a compound derived from the traditional Chinese medicine plants, inhibits endoplasmic reticulum stress-mediated phagocytosis in steatotic liver transplantation. It is the first report that addresses the protective function of BBR on steatosis liver transplantation, but the specific mechanism involved still remains unclear [ 23 ]. Besides, saffron ethanol extract can also relieve the endoplasmic reticulum stress and protein ubiquitination induced by liver I/R [ 8 ].…”
Section: The Protective Effect Of Tcms On Liver Ischemia-reperfusion Injury and Potential Mechanismsmentioning
confidence: 99%